OP03 Does a complex intervention by primary care nurses increase walking in 60–75 year olds? Outcomes at three and twelve months from the PACE-Lift (Pedometer Accelerometer Consultation Evaluation – Lift) cluster randomised controlled trial. (2nd September 2014) - Harris, T; Kerry, S; Victor, C; Ekelund, U; Woodcock, A; Iliffe, S; Whincup, P; Beighton, C; Ussher, M; Limb, E; David, L; Brewin, D; et al.
Abstract : Background: Physical activity is vital for older people's health. Walking is older people's commonest physical activity (PA), light intensity if strolling, moderate intensity if brisker. We assessed whether a primary care nurse-delivered complex intervention increased older peoples' walking. Methods: 2-arm parallel design, cluster randomised controlled trial with household as the randomisation unit. 988 people aged 60–75 years who had no restrictions to increasing their walking, were randomly selected from 3 Oxfordshire and Berkshire UK general practices and invited to participate, of whom 298 people from 250 households were randomised to intervention group (150 individuals) or usual care control group (148 individuals). The intervention group received four practice nurse PA consultations incorporating behaviour change techniques, feedback on pedometer step-counts and accelerometer PA intensity, an individual PA diary and PA plan. Outcomes were: average daily step-counts over 7 days (primary outcome) and average time spent in moderate or vigorous PA weekly (MVPA) (secondary outcome) at 3 and 12 months, assessed by accelerometry. These were regressed on baseline levels to represent changes. Other outcomes included adverse events, anthropometry, depression, anxiety and pain scores. Assessors were not blind to group allocation. Trial Registration Number: ISRCTN421225561 Results: Primary outcome data were available for 280 (94%) individuals. Mean (SD) baseline average daily step-count was 7453 (2463) in control and 7388 (2218) in intervention groups. At 3 months both average daily step-counts and average weekly MVPA increased significantly more in the intervention than control group, by 1037 (95% CI 513, 1560) steps/day and 66 (95% CI 36, 96) minutes/week respectively. At 12 months the corresponding differences were 609 (95% CI 104, 1115) steps/day and 40 (95% CI 10, 70) minutes/week respectively. There were no significant between group differences in other outcomes. Conclusion: The PACE-Lift trial increased walking, both step-counts and time spent in MVPA in older primary care patients at 3 and 12 months, with no effect on adverse events.